2018
DOI: 10.4236/as.2018.99078
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Quality of Milk Fatty Acid in Dairy Cows Supplemented with Soybean Oil and DHA-Micro Algae in a Confined Production System

Abstract: The objective was to reduce saturated fatty acids (SFA) and increase conjugated linoleic acid (CLA, cis-9, trans-11 C 18:2 ), α-linolenic (cis-9, cis-12, cis-15

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
15
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 44 publications
8
15
3
Order By: Relevance
“…A lower milk fat content (−5.4%) was also detected (P < 0.11) in samples taken from the tank reflecting an overall negative effect of oil intake over the total herd. Milk fat content decrease (9.24% to 5.4%) was close to the average value of 8% reported for grazing dairy cows [26] but lower than the 28.6% observed in our previous work using the SO (0.72 kg•cow −1 •day −1 ), micro-algae (0.144 kg•cow −1 •day −1 ) combination [20].…”
Section: Milk Yield and Compositionsupporting
confidence: 81%
See 4 more Smart Citations
“…A lower milk fat content (−5.4%) was also detected (P < 0.11) in samples taken from the tank reflecting an overall negative effect of oil intake over the total herd. Milk fat content decrease (9.24% to 5.4%) was close to the average value of 8% reported for grazing dairy cows [26] but lower than the 28.6% observed in our previous work using the SO (0.72 kg•cow −1 •day −1 ), micro-algae (0.144 kg•cow −1 •day −1 ) combination [20].…”
Section: Milk Yield and Compositionsupporting
confidence: 81%
“…The absence of a net depressant effect (P = 0.19) of supplementary PUFA on butyric acid (C 4:0 ) content of Mod-Milk (Table 4) was also observed in our previous study [20] being a result frequently reported [28]. This FA is only found in ruminant milk and has shown antineoplasic effects inhibiting the development of mammary carcinoma in rats [39] and hence is considered to play a potential beneficial role in human health.…”
Section: Milk Fatty Acid Profilesupporting
confidence: 75%
See 3 more Smart Citations